2007
DOI: 10.4161/cc.6.1.3699
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Abrogation of S-Phase Checkpoint Enhances the Anti-Tumor Activity of Gemcitabine In Vivo

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=3699 KeY WORDSCHK1, CHK2, EXEL-9844, XL844, S-phase checkpoint, gemcitabine ABBReviATiONS ATRATM and Rad3-related kinase TGI tumor growth inhibition MBP myelin basic protein ABSTRACTChk1 and Chk2 kinases are critically involved in modulating DNA damage checkpoints. In particular, Chk1, a key activator of the S-phase DNA damage response, may be involved in resistance to genotoxic therapies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 36 publications
6
90
1
Order By: Relevance
“…31 In cells treated with gemcitabine, Chk1 inhibition abolishes S-phase checkpoint 27,32 and causes premature mitosis. 26,27,33,34 However, a previous study indicated a lack of correlation between premature mitotic entry and cytotoxicity 35 bringing into question the mechanism for chemosensitization by Chk1 inhibitors. cells treated with gemcitabine and AZD7762 was likely due to reduced total Chk1 protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In cells treated with gemcitabine, Chk1 inhibition abolishes S-phase checkpoint 27,32 and causes premature mitosis. 26,27,33,34 However, a previous study indicated a lack of correlation between premature mitotic entry and cytotoxicity 35 bringing into question the mechanism for chemosensitization by Chk1 inhibitors. cells treated with gemcitabine and AZD7762 was likely due to reduced total Chk1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 The kinase mediating the increase in γH2AX and how it relates to the effect of Chk1 inhibition on stalled replication forks have not been elucidated.…”
Section: Chk1 Inhibition After Replicative Stress Activates a Double mentioning
confidence: 99%
“…In a CML nude mice survival model, the combination of XL844 and daunorubicin caused a significant increase in median survival time. In a panel of multiple solid tumour cell lines, XL844 had little effect as a single agent, but substantially increased the cytotoxicity of gemcitabine (Matthews et al, 2007). XL844 was shown to affect both the S and G2 checkpoints by blocking gemcitabine-induced DSBs and CDC25A phosphorylation, inducing premature mitotic entry.…”
Section: Xl844mentioning
confidence: 99%
“…For example, nucleoside analog exposure causes the phosphorylation of the DNA damage responsive histone, H2AX, which forms nuclear foci at sites of stalled replication forks (Figure 3). Upon checkpoint abrogation of gemcitabine-induced S phase arrested cells by inhibition of Chk1, H2AX phosphorylation further increases by 10-fold and is associated with a decrease in clonogenic survival (Matthews et al, 2007;Ewald et al, 2007), thus suggesting lethal increases in DNA damage. A similar effect was observed after only a 2-h exposure to gemcitabine.…”
Section: Checkpoint Dysregulationmentioning
confidence: 99%
“…In experimental systems, pharmacological inhibition of Chk1 in nucleoside analog-arrested cells results in rapid abrogation of the checkpoint, enhanced DNA damage and increased apoptosis Liu et al, 2005;Xiao et al, 2005;Matthews et al, 2007;Ewald et al, 2007).…”
Section: Checkpoint Dysregulationmentioning
confidence: 99%